2022
DOI: 10.5114/fn.2022.122342
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inflammation-related degenerative changes on the wall strength of unruptured intracranial aneurysms: a pilot study

Abstract: Introduction: Saccular intracranial aneurysm (sIA) rupture is a serious cerebrovascular event associated with inflammatory destructive processes leading to gradual weakening of the sIA wall. The aim of the present study was to identify the morphological and histological determinants for low wall strength in unruptured sIAs harvested from autopsy subjects. Material and methods: A total of eight single unruptured sIAs were identified and excised with adjacent cerebral arteries during 8 of 184 postmortem examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Factors such as turbulent bloodflow and altered shear forces may possibly contribute to locally elevated biomarker levels [40]. Previous studies have indicated that these haemodynamic alterations can lead to endothelial dysfunction, vascular remodelling, and the production of inflammatory proteins, resulting in elevated biomarker concentrations [41].…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as turbulent bloodflow and altered shear forces may possibly contribute to locally elevated biomarker levels [40]. Previous studies have indicated that these haemodynamic alterations can lead to endothelial dysfunction, vascular remodelling, and the production of inflammatory proteins, resulting in elevated biomarker concentrations [41].…”
Section: Discussionmentioning
confidence: 99%